Beyond the Single Path View: Interpath Dynamics in Regional Contexts. (1st January 2020) - Frangenheim, Alexandra; Trippl, Michaela; Chlebna, Camilla
Abstract: Recurrent economic and financial crises, globalization, digitalization, and climate change are posing major challenges for regional economies to constantly renew their industrial structures. Over the past few years much progress has been made in understanding how new path development unfolds in a regional context. Earlier contributions to the path development literature have acknowledged that multiple industrial paths developing within a region are interdependent and coevolving. However, most conceptualizations and empirical analyses to date have mainly been focused on one new path or path development activities in one nascent industry only. Potential relationships between emerging paths have received little attention, and, as a consequence, little is known about how new paths shape each other's evolution. This article draws on recent contributions that broaden conventional perspectives on regional structural change and develops a framework to analyze the dynamic interdependencies between multiple new regional growth paths. We explore the nature of interpath linkages and discuss the role of agency in creating or shaping the relationship between linked paths to be either supportive, competitive, or neutral toward each other. By means of illustrative empirical examples, we show that interpath relationships in a regional context are a significant phenomenon to be considered in regional structural change and conclude by discussing policy implications and identifying avenues for future research.